Importância de Ureaplasma Urealyticum e Mycoplasma Hominis em materiais "Uro-genitais" - Ceccarelli, Vaoira Regina da S. M.; Kuriki, Kiyoko Horie; Vinagre, Agda C.P.; Yara, Teresa L. (Brazilian Journal of Sexually Transmitted Diseases, 1995)
Isolated Ureaplasma urealyticum and lvfycoplasma hominis i n urogenital tract are associated with Sexually Transmitted Diseases (S.T.D.), Non Gonococcal Urethritis, Pelvic Inflammatory Disease, Neonatal Infections, Spontaneous Abortions and Infertility Cases. July 1994, by the Bio-Ciência/Lavoisier, in 1.427 cultures proceeding from vaginal, urethral, endocervical secreta, urine and sperm presented a positiveness of30.8% (440) in Ureaplasma urealyticum and 6.1 % (87) inMycoplasma hominis. The identification of Ureaplasma urealyticum was based on activity of urease and brown-golden colonies observation in solid media. TheJvJycoplasma hominis was characterized by arginine and colonial morphology. It is important emphasizing that the greater incidence of positiveness found for Ureaplasma urealyticum was of 34.3% in Endocervical secreta and 32.5% in Vaginal secreta, followedby26,3% in Urethral secreta. Undoubtedly theMycoplasma hominis and Ureaplasma urealyticum are important pathogenes and, therefore, they must be searched and whatever is found, valorized with colonization higher than 10 U.F. C.